Analis Pemanfaatan Media Pembelajaran IPA Di Kelas V MI Tarbiyatul Athfal - Fitriya, Maulida; Azhar, Arry Patriasurya; Perdiansyah, Ferry (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to analyze the use of science learning media in class V, how to use science learning media in class V, what problems are encountered in using science learning media in class V and what efforts are being made to overcome the problem of using science learning media in class V. Science learning media includes visual media, audio-visual media and concrete media that teachers use in the learning process. This research was conducted at MI Tarbiyatul Athfal, South Tangerang. This study used a qualitative research method with a qualitative descriptive research type, the subjects in this study were school principals, class V teachers and fifth grade students, while the object of this study was the use of science learning media in class V MI Tarbiyatul Athfal, data collection techniques in the form of observation , interviews and documentation of learning media. The results of the research show that the learning media used by the teacher are blackboards, concrete objects, printed pictures, printed books.